MANAJEMEN MUTU PENDIDIKAN DASAR: PENDEKATAN TQM DAN EDM - Muthiyah Salsabilah; Suardi; Idawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The urgency of this study arises from the suboptimal integration of Total Quality Management (TQM) principles and School Self-Evaluation (EDM) in managing the quality of basic education, particularly in ensuring continuous, data-driven improvement. Previous studies have predominantly examined TQM or EDM separately, resulting in a limited understanding of their combined implementation within elementary school contexts. This study aims to analyze the implementation of basic education quality management through the integration of TQM and EDM, as well as to identify the supporting and inhibiting factors influencing its application. A descriptive qualitative approach was employed, utilizing in-depth interviews, observations, and document analysis as primary data collection techniques. The collected data were analyzed using thematic analysis. The findings indicate that EDM functions as a strategic foundation for quality planning and control through the PPEPP cycle (Establishment, Implementation, Evaluation, Control, and Improvement), which aligns closely with core TQM principles such as continuous improvement, stakeholder involvement, and evidence-based decision making. These results imply that the integration of TQM and EDM strengthens a systematic and sustainable quality management system in elementary schools. The novelty of this study lies in an integrative conceptual framework that positions EDM as a strategic instrument in the implementation of TQM within basic education, an area that has received limited scholarly attention. This research contributes theoretically to the advancement of educational quality management studies and practically provides guidance for schools and policymakers in improving basic education quality through self-evaluation-based management.